SEJARAH DAN ISTILAH – ISTILAH EKONOMI ISLAM - subhan arif (Ath Thariq Jurnal Dakwah dan Komunikasi, 2018)
The thought of Islamic Economics began since the Prophet Muhammad. Appointed as an Apostle (messenger of Allah), several policies carried out by the Prophet Muhammad SAW related to the implementation of community life at that time, in addition to the issue of fiqh, politics, as well as commercial or economic problems. The economic problems of the Islamic ummah at that time were of concern to the Prophet, because economic problems were the pillars of the faith that must be considered carefully for the benefit of the world and in the future. Poverty will bring people to disbelief, so efforts to eradicate poverty are parts of social policies issued by the Prophet Muhammad.